Identificación y evaluación de los factores de riesgo psicosocial y estrés en despachadores de vuelo (2019)
Objetive: the research that is presented below describes the main psychosocial risk factors intra-labor in a group of air dispatchers carried out in a Colombian airline. Method: The identification of psychosocial risk factors intra-labor is done by means of the application of the Instrument Battery for the Evaluation of Psychosocial Risk Factors elaborated by the Pontificia Universidad Javeriana Bogotá at the request of the Ministry of Social Protection (2010), taking into account the 4 domains and the 19 dimensions that are part of the intra-laboratory construct and from these identify the factors at greatest risk and the level of perceived stress. Analysis: a qualitative analysis of the quantitative data obtained through the test is carried out, allowing to identify and infer about possible causes related to those conditions that are considered risk for flight dispatchers. Conclusions: It was possible to recognize that the work can be considered with a high level of risk, compared to the various psychosocial factors related to their environment, which lead them to have a high perception and manifestation of stress